1995
DOI: 10.1007/bf00011787
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar and planting date effects on soybean root growth

Abstract: To avoid late summer drought, soybean [Gylcine max (L) Merrill] producers in many southern and border states of the USA modify their cropping systems. Options include use of unadapted cultivars and changing planting dates. Because root function is important to plant health and yield, this study was conducted to determine if planting date and soybean cultivar affect root growth and distribution. Seeds of one cultivar from each of four maturity groups (MG III, IV, V, and VI) were sown in mid-April, mid-May, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(16 reference statements)
1
4
0
1
Order By: Relevance
“…However, maturity groups did not influence any root traits [P-values for the effect of maturity groups on total root length, total root surface area, total root volume, average root diameter, fine root length, and fine root surface area were 0.72, 0.54, 0.35, 0.06, 0.74, and 0.51, respectively, and for root penetration, 0.19 (Run 1) and 0.89 (Run 2)]. Similar observations were made by Turman et al [ 56 ], who observed that root length density (total root length in unit soil volume) of soybean was not related to maturity groups under field conditions.…”
Section: Discussionsupporting
confidence: 87%
“…However, maturity groups did not influence any root traits [P-values for the effect of maturity groups on total root length, total root surface area, total root volume, average root diameter, fine root length, and fine root surface area were 0.72, 0.54, 0.35, 0.06, 0.74, and 0.51, respectively, and for root penetration, 0.19 (Run 1) and 0.89 (Run 2)]. Similar observations were made by Turman et al [ 56 ], who observed that root length density (total root length in unit soil volume) of soybean was not related to maturity groups under field conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Considering the importance of root function to soybean plant growth, Turman et al (1995b) found that mid‐May planted soybean in Missouri had more extended root depth at 30 d after emergence than mid‐June and early July planting. Another experiment conducted by Turman et al (1995a) indicated that earlier than normal planting date of four maturity groups (MG III, IV, V, and VI) soybean inhibited early root growth, but did not reduce yield, suggesting that the root may not be an important factor in cultivar selection.…”
Section: Soybean Growth and Yieldmentioning
confidence: 99%
“…This result is consistent with the findings of Tsegaye et al (1995), who estimated a root elongation rate of the main root axis of between 0.015 and 0.021 m day )1 and those of Tricot et al (1997), who reported a root elongation rate of 0.022 m day )1 . Pea RSER was within the range of variation observed for winter wheat, for which an RSER of 0.012 m day )1 has been observed ( Barraclough and Leigh, 1984) and soybean, for which RSER has been reported to vary from 0.004 to 0.013 m day )1 (Turman et al, 1995).…”
Section: Root System Elongation Ratementioning
confidence: 58%
“…Thus, changes in crop management (particularly the sowing period) should make it possible to increase pea root depth and reduce the risk of water stress at the end of the cycle, as shown for soybean (Taylor, 1980), potentially increasing yield stability and seed protein content. The effects on root development of seasonal variations in temperature and radiation due to spring or autumn sowing have never been compared as most previous studies (Barraclough and Leigh, 1984;Vincent and Gregory, 1989b;Turman et al, 1995) have compared root growth and development in field conditions for different sowing dates in the same season only. The effect of highly contrasted sowing dates (autumn and spring) has yet to be investigated in field conditions.…”
Section: Introductionmentioning
confidence: 97%